Spare Parts Supplier Selection Design: A Case Study of A Railway Company - Robby Ady Asmara; Lien Herliani Kusumah (Jurnal Optimasi Sistem Industri, 2021)
Spare parts support is essential for rolling stock maintenance management. The current supplier selection model determines the selected supplier based on evaluating one aspect of the criteria (product aspect). The selection of suppliers with poor performance occurred between 2018-2020 related to the delivery of goods that exceeded the deadline and goods that did not meet specifications. The first objective of this research is to analyze and determine the relevant priority criteria for selecting suppliers of rolling stock spare parts for railway companies. The second objective is to determine the rolling stock spare parts supplier by using the evaluation criteria determined in the previous process. The method used in this research is the integration of the Fuzzy Delphi Method (FDM), Analytical Hierarchy Process (AHP), and Technique for Others Preference by Similarity to Ideal Solutions (TOPSIS). FDM is used to select important criteria for the selection of suppliers of rolling stock parts. AHP is used to assist in choosing various criteria through evaluation in determining the criteria's weight. TOPSIS is used to assess supplier ratings. A total of 13 criteria from 19 alternative criteria have been selected for railway companies, especially in selecting rolling stock spare parts suppliers. Furthermore, the selection becomes the basis for bidding. Finally, Supplier A is the supplier with the highest relative closeness value (0.591), followed by Supplier B (0.545), and the lowest is Supplier C (0.282).